2019
DOI: 10.1088/1748-9326/ab20d4
|View full text |Cite
|
Sign up to set email alerts
|

Shifting landscapes: decoupled urban irrigation and greenness patterns during severe drought

Abstract: Urban outdoor water conservation and efficiency offer high potential for demand-side management, but irrigation, greenness, and climate interlinks must be better understood to design optimal policies. To identify paired transitions during drought, we matched parcel-level water use data from smart, dedicated irrigation meters with high-spatial resolution, multispectral aerial imagery. We examined changes across 72 non-residential parcels using potable or recycled water for large landscape irrigation over four b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…(2012) identify a 1.4% increase in water consumption for every 1°F increase in nighttime temperature in Phoenix, Arizona, highlighting the importance of feedbacks between the built environment and urban vegetation. However, recent studies have shown that during drought, urban irrigation and greenness can become decoupled, and increases in irrigation do not result in maintained vegetation greenness through the duration of a drought for any vegetation type (Miller et al., 2020; Quesnel et al., 2019). Because vegetation responds most strongly to climate signals, increased outdoor water use in a hotter climate is unlikely to maintain verdant, lush vegetation, prompting continued overapplication of urban irrigation or adaptation of urban vegetation regimes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2012) identify a 1.4% increase in water consumption for every 1°F increase in nighttime temperature in Phoenix, Arizona, highlighting the importance of feedbacks between the built environment and urban vegetation. However, recent studies have shown that during drought, urban irrigation and greenness can become decoupled, and increases in irrigation do not result in maintained vegetation greenness through the duration of a drought for any vegetation type (Miller et al., 2020; Quesnel et al., 2019). Because vegetation responds most strongly to climate signals, increased outdoor water use in a hotter climate is unlikely to maintain verdant, lush vegetation, prompting continued overapplication of urban irrigation or adaptation of urban vegetation regimes.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of outdoor water use remain largely uncertain due to inconsistent calculation methods, lack of metering, and limited data (Anda et al., 2013; Boyle et al., 2013; Gleick et al., 2003). Dual metering, with dedicated irrigation meters, is becoming a more common practice and a promising component of outdoor water use evaluations and conservation management (Quesnel & Ajami, 2019; Quesnel et al., 2019). However, implementation of dual metering is limited in scope and often excludes single‐family residential properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outdoor water use is more elastic and discretionary than other water use categories and can theoretically be curtailed rapidly in response to climate signals (Breyer et al, 2018; Espey et al, 1997; Lyman, 1992). Fresh findings also suggest that reducing the use of city water outdoors need not come at a high environmental cost: Research from California suggests that the health of urban greenspaces is largely decoupled from irrigation water use during drought episodes and that the greenness of those landscapes can rebound rapidly once the rains return (Quesnel et al, 2019). Turfgrass species commonly used in urban landscaping are especially adept at surviving summer drought stresses, so reducing irrigation of urban greenspaces during periods of low water availability can potentially be achieved without sacrificing their long‐term health (Beard & Green, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The value of a time‐series analysis of multispectral imagery to characterize vegetation is recognized by the United States (U.S.) Department of Agriculture’s National Agricultural Imagery Program (NAIP), which collects nationwide, multispectral imagery every two years during the late summer since 2003 (Grant 2018). More recently, time‐series analysis of NAIP imagery has been used to delineate natural from artificial turf and track changes to natural turf vigor as a result of decreased irrigation (Quesnel et al 2019).…”
Section: Introductionmentioning
confidence: 99%